Evaluating the prevalence, type and the probable causes for sport injuries in Iranian Super League male volleyball players - Rajabi, R.; Alizadeh, M. H.; Hosseinian, M. Z. (World Journal of Sport Sciences, 2009)
In this study, the prevalence, type and the probable causes of sport injuries in Iranian super league male volleyball players was evaluated. The study was descriptive and the statistical population was about 160 volleyball players that were present in Iran super league in the year 2005. The statistical sample was about 60 men with at least three years of experience in volleyball. The information was gathered using a combined questionnaire by interviewing the volleyball players and their coaches. During the training and competition seasons, lower limbs with 44% and 46.8% were the most vulnerable organs to injuries. During training, joint injuries with 46.1% and during competition, muscular injuries with 43.5% were the most common kinds of injury. During training and competition, sprain with 46.8% and 38.6% was the most common joint injury and spasm with 42% and 37.3% was the most common muscular injury. During training, fracture with 49.4% and during competition, the close fracture with 54.6% were the most common bone injuries. During training and competition, fingers with 42.8% and 44.9% were the most vulnerable organs of upper limbs, ankle with 33.1% and 38.3% the most vulnerable organ of lower limbs and lumbar with 68.6% and 75% the most vulnerable organ of trunk, head and neck to be injured. During training and competition, sprain with 23% and 20% was the most common kind of injury as a whole. During training, fingers with 15.58% and during competition, ankle with 17.4% were the most vulnerable organs of all body to be injured; and each considered probable factors with different effects caused injuries. The study revealed that body building in volleyball, ground/surface condition and quality of personal equipment could be important factors to be associated with the injuries in this sport. Eventually, it was concluded that fingers, lumbar and ankle were the most vulnerable organs and injuries which were mostly the result of overusing organs with incorrect techniques. Therefore, correcting the techniques might play a considerable role in the prevention of injuries.